Evaluation of the Operational, Economic, and Environmental Benefits of Adopting Blue Economy in the Change of Aircraft Engine Washing Process: A Case Study - Flavio Luiz Rodrigues; Geraldo Cardoso Oliveira Neto; Henrricco Nieves Pujol Tucci; Luiz Fernando Rodrigues Pinto; Francesco Facchini (Engineering Reports, 2025)
ABSTRACT The aviation industry has a significant impact on the environment, accounting for 13% of global fossil fuel consumption and 2% of annual CO2 emissions. One of the factors that increase this consumption is engine degradation due to the accumulation of dirt on compressor blades. To mitigate this effect and restore efficiency, compressor washing is essential, but it requires high water consumption. This study analyzes the operational, economic, and environmental benefits of optimizing this process, based on the Blue Economy. Fuel efficiency was assessed using the Fuel/RTM indicator, financial viability using ROI, and environmental impacts using the MIF index. The results indicate a 1.8% gain in fuel efficiency, annual savings of $179,000, a 6.9% reduction in environmental impact, and a 50% drop in water use. The findings demonstrate that sustainable maintenance practices generate economic and environmental gains, contributing to the conservation of water resources in aviation.